Matriptase promotes inflammatory cell accumulation and progression of established epidermal tumors - Sales, Katiuchia Uzzun (Oncogene, 2014)
Deregulation of matriptase is a consistent feature of human epithelial cancers and correlates with poor disease outcome. We have previously shown that matriptase promotes multi-stage squamous cell carcinogenesis in transgenic mice through dual activation of pro-hepatocyte growth factor-cMet-Akt-mTor proliferation/survival signaling and PAR-2-Gαi-NFκB inflammatory signaling. Matriptase was congenitally and constitutively deregulated in our prior studies, and therefore it was unclear if aberrant matriptase signaling supports only initiation of tumor formation or if it is also critical for the progression of established tumors. To determine this, we here have generated triple-transgenic mice with constitutive deregulation of matriptase and simultaneous inducible expression of the cognate matriptase inhibitor, hepatocyte growth factor inhibitor (HAI)-2. As expected, constitutive expression of HAI-2 suppressed the formation of matriptase-dependent tumors in 7,12-Dimethylbenz(a)anthracene (DMBA)-treated mouse skin. Interestingly, however, the induction of HAI-2 expression in already established tumors markedly impaired malignant progression and caused regression of individual tumors. Tumor regression correlated with reduced accumulation of tumor-associated inflammatory cells, likely caused by diminished expression of pro-tumorigenic inflammatory cytokines. The data suggest that matriptase-dependent signaling may be a therapeutic target for both squamous cell carcinoma chemoprevention and for the treatment of established tumors.